Making space for multilingualism in Australian schooling. (3rd July 2016) - Turner, Marianne; Cross, Russell
Abstract: In this article we introduce the special issue: Language(s) across the curriculum in Australian schools. The special issue includes a focus on English as an additional language in mainstream classes, Indigenous education, heritage languages and foreign languages, and we give background to these different – though frequently overlapping – contexts. By considering context, we seek to demonstrate the timeliness and importance both of the special issue and of a focus on the experiences of students, teachers, parents and members of the community in bilingual and multilingual initiatives. Despite the empirical focus being Australian schools, we understand that the findings may resonate with other setting where monolingual ways of thinking are dominant. We conclude this introductory article by providing the structure and overview of the special issue.